2020
DOI: 10.3389/fpls.2020.00579
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and Cellular Distribution of Phosphate in the Diatom Phaeodactylum tricornutum

Abstract: Unicellular organisms that live in marine environments must cope with considerable fluctuations in the availability of inorganic phosphate (P i). Here, we investigated the extracellular P i concentration-dependent expression, as well as the intracellular or extracellular localization, of phosphatases and phosphate transporters of the diatom Phaeodactylum tricornutum. We identified P i-regulated plasma membrane-localized, ER-localized, and secreted phosphatases, in addition to plasma membrane-localized, vacuola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Some VTC proteins (Phatrdraft_48811, 35739, 50019) show a non-vacuolar localization when expressed as eGFP proteins, being integrated most likely in the endomembrane system or in not specified compartments in case of Phatrdraft_48538 (Dell'Aquila et al 2020). Despite this, independently to the result described in Alipanah et al 2018, we identified the afore-mentioned vacuolar transporter Phatrdraft_19586, and localized it in the tonoplast (Dell'Aquila et al 2020).…”
Section: Phosphate Storagementioning
confidence: 57%
See 4 more Smart Citations
“…Some VTC proteins (Phatrdraft_48811, 35739, 50019) show a non-vacuolar localization when expressed as eGFP proteins, being integrated most likely in the endomembrane system or in not specified compartments in case of Phatrdraft_48538 (Dell'Aquila et al 2020). Despite this, independently to the result described in Alipanah et al 2018, we identified the afore-mentioned vacuolar transporter Phatrdraft_19586, and localized it in the tonoplast (Dell'Aquila et al 2020).…”
Section: Phosphate Storagementioning
confidence: 57%
“…A fourth P-regulated putative alkaline phosphatase (Phatrdraft_45757) was shown to be an enzyme of the endoplasmic reticulum (ER) and a membrane surrounding the plastid of diatoms (chloroplast-ER, cER). The latter finding might indicate P scavenging activities in internal compartments as well, especially in the phospholipid (PL) degradation pathway under P-starvation, as proposed by Dell'Aquila et al (2020). P. tricornutum might use further P scavenging strategies.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations